2014
DOI: 10.1039/c4cp04489d
|View full text |Cite
|
Sign up to set email alerts
|

Pt-free tandem molecular photoelectrochemical cells for water splitting driven by visible light

Abstract: Photoelectrochemical (PEC) cells using molecular catalysts to split water into hydrogen and oxygen have been investigated intensively during the past years. However, the high-cost of Pt counter electrodes and instability of molecular PEC cells hinder the practical applications. We describe in this article a Pt-free tandem molecular PEC cell, for the first time, employing molecular ruthenium- and cobalt-catalysts with strong dipicolinic acid anchoring groups on the respective photoanode and photocathode for tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
170
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(177 citation statements)
references
References 21 publications
7
170
0
Order By: Relevance
“…[41] To improvet he stability of the catalysto nt he NiO surface, Sun and co-workersi ntroduced pyridine-2,6-dicarboxylic acid (PDA)a sastrong and stable anchoring group in both aH 2 evolution catalyst (CoHEC)a nd an O 2 evolution catalyst (RuOEC) (see Figure 4). [41] To improvet he stability of the catalysto nt he NiO surface, Sun and co-workersi ntroduced pyridine-2,6-dicarboxylic acid (PDA)a sastrong and stable anchoring group in both aH 2 evolution catalyst (CoHEC)a nd an O 2 evolution catalyst (RuOEC) (see Figure 4).…”
Section: Water/proton Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[41] To improvet he stability of the catalysto nt he NiO surface, Sun and co-workersi ntroduced pyridine-2,6-dicarboxylic acid (PDA)a sastrong and stable anchoring group in both aH 2 evolution catalyst (CoHEC)a nd an O 2 evolution catalyst (RuOEC) (see Figure 4). [41] To improvet he stability of the catalysto nt he NiO surface, Sun and co-workersi ntroduced pyridine-2,6-dicarboxylic acid (PDA)a sastrong and stable anchoring group in both aH 2 evolution catalyst (CoHEC)a nd an O 2 evolution catalyst (RuOEC) (see Figure 4).…”
Section: Water/proton Reductionmentioning
confidence: 99%
“…Reproduced and modified from Ref [41]. b) Energy levels and electron/hole-transferp rocesses occurring in the tandem molecularP EC cell.…”
mentioning
confidence: 99%
“…[13][14][15][16][17][18][19][20] In the pioneer work, it was found that the organic dye-sensitized NiO photocathodes with or without HER catalyst displayed low photocurrent and poor stability in the HER. 13,14 Chemically bonding both a ruthenium polypyridylchromophore and a cobaloxime catalyst to the NiO film, either with a cascade or 3 a parallel linkage, provided more stable NiO-based photocathode, which displayed the photocurrents of about 13−20 μA cm −2 at an applied potential of −0.2 V vs. NHE (the potentials mentioned hereafter are versus NHE if not specially denoted) for the HER.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Chemically bonding both a ruthenium polypyridylchromophore and a cobaloxime catalyst to the NiO film, either with a cascade or 3 a parallel linkage, provided more stable NiO-based photocathode, which displayed the photocurrents of about 13−20 μA cm −2 at an applied potential of −0.2 V vs. NHE (the potentials mentioned hereafter are versus NHE if not specially denoted) for the HER. 15,16 The reason for the low activities of these sensitized NiO photocathodes may stem from several factors: (i) the small hole diffusion coefficient in NiO, 21,22 (ii) the competition of the hole injection from a sensitizer to the valence band of NiO with the fast recombination between the reduced dye and the holes generated in NiO, and (iii) poor sensitizer loading dominantly due to the low specific surface area of NiO. Some recent studies showed that compared to dye-sensitized NiO photocathodes, the quantum dot (QD)-sensitized NiO cathodes exhibited much larger hole diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…To avoid the use of any sacrificial agent and generate H 2 in an environmentally friendly manner, photoelectrochemical (PEC) 40 production of H 2 is an ideally clean and renewable mean that integrates solar energy collection and water reduction into a single photoelectrode. [24][25][26][27][28][29] In fact, the recent interest in utilizing QDs for harvesting light energy offers new ways to control light conversion efficiency in the solar cells. [30][31][32][33] However, PEC 45 studies involving QDs-sensitized photoelectrodes have focused almost exclusively on photoanodes, where photocurrents result from light-simulated electron transfer from QDs into the conduction bands of an n-type semiconductor, such as TiO 2 .…”
mentioning
confidence: 99%